PENGARUH PROFESIONALISME GURU DAN KREATIVITAS SISWA TERHADAP HASIL BELAJAR SISWA KELAS VI SE KAPANEWON PLERET, YOGYAKARTA - Rina Yiliatun; Aji Permana, Septian; Dodi Sukmayadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the influence of Teacher Professionalism and Student Creativity on the Learning Outcomes of Class VI Students of Kapanewon Pleret Yogyakarta. This study was conducted from December 2023 to January 2024. The research method used is quantitative research by means of In this study the sample was grade VI students in each cluster in Kapanewon Pleret, Bantul Regency which was calculated using a random sampling technique totaling 84 people determined by the Solvin formula. The results of this study indicate that the t-test results show that individually if teacher professionalism and student creativity each have a positive and significant influence on learning outcomes. The variable of teacher professionalism is more dominant than student creativity in influencing student learning outcomes. The results of the F test show that teacher professionalism and student creativity have a positive effect on the learning outcomes of Class VI students of Kapanewon Pleret. The results of the determinant analysis show that the variables of teacher professionalism and student creativity each have a sufficient correlation with learning outcomes. Both variables are able to explain their influence on learning outcomes by 39% while 61% is explained by other variables outside the research concept.